THE ROLE OF NOVELTY SEEKING, CULINARY EXPERIENCE QUALITY AND DESTINATION IMAGE IN FORMING TOURIST SATISFACTION TOWARD THE INTENTION TO REVISIT KOTA PONTIANAK - Barkah, Barkah; Febriasari, Puty (Department of Management, Faculty of Economics, Universitas Negeri Semarang, 2021)
Previous findings indicate that novelty-seeking experience through travel is one of the keys to satisfaction. In the context of tourism, destination image and satisfaction are commonly used as determinants of tourist revisit intention in various tourism settings. This research was designed to re-examine the formation of tourists satisfaction and their motivation to revisit Kota Pontianak based on their experience on the previous trip. Novelty seeking, destination image, and culinary experience quality was proposed to be the predictor of tourist satisfaction and their revisit intention. The results using SEM-PLS showed that basically tourists satisfaction and their revisit intention is determined by their experience quality in the previous trip and the city’s destination image. The coefficient of determination of the tourists culinary experience quality and the city’s destination image in the research model is quite small, therefore it still needs more research to identify the factor that influence tourists satisfaction and their revisit intention in the tourism context.